Validitas Kuesioner Kesadaran Gizi Keluarga Pada Ibu Dengan Anak Stunting di Kabupaten Jember: Validity of the Nutritional Awarness of Family Questionnaire for Mothers’ Children with Stunting in Jember Regency - Tantut Susanto; Grysha Viofananda Agung Kharisma Ade; Hanny Rasni (Madago Nursing Journal, 2023)
Introduction: Low family nutrition awareness will have an impact on nutritional problems in family members. Mothers as the main caregivers in the family are very decisive in the problem of stunting in children under five. This study was to describe the validity of Nutritional Awareness of Family Questionnare (NAF-Q) that measures level of awareness of family to prevent stunting children. Methods: A cross-sectional study of Panti (Indonesian) was conducted among parents with stunting under five children (n = 167). Multifactors NAF-Q were examined using content validity (Content Validity Index [CVI]). Internal consistency was explored using Cronbach’s α coefficient. Results: The CVI indicated adequate content validity (0.80–1.00) and acceptable internal consistency (0.896). Conclusions: NAF-Q contains valid, reliable, and robust measures although some subscales performed high reliability, establishing the purpose for further research.